Broadening perfect sound absorption by composite absorber filled with porous material at low frequency. (February 2022) - Cheng, Baozhu; Gao, Nansha; Huang, Yunke; Hou, Hong
To enhance the low-frequency broadband sound absorption, we propose an absorber filled with porous material and establish a relative acoustic model. Based on the critical coupling condition, a Helmholtz absorber was designed to achieve perfect sound absorption at 172 Hz by the complex frequency plane method. Considering the weak adjustability and acoustic impedance of the Helmholtz absorber, we devised four absorber filled with porous material units that can achieve perfect sound absorption at discrete frequencies between 400 and 488 Hz with a thickness of only 51 mm. A composite absorber filled with porous material was designed by arranging four absorber filled with porous material units in a coplanar manner. The broadband perfect sound absorption of the composite absorber filled with porous material was subsequently verified by simulation and experiment. The thickness of the composite absorber filled with porous material is only 1/18 of the wavelength corresponding to the perfect absorption frequency, and it shows excellent subwavelength characteristics. The theoretical acoustic model of the composite absorber filled with porous material and the complex frequency plane method can achieve a more efficient design of broadband perfect sound absorbers. The composite absorber filled with porous material not only realizes low-frequency broadband perfect sound absorption but is also lightweight and easy to fabricate. This demonstrates the composite absorber filled with porous material structure has great potential for application in low to mid frequency noise control.